A Literature Review of UI/UX Design Concepts and Their Role in Web and Mobile Application Development - Marsha Pelisiani; Nur Safitri Siregar; Hendri Purnomo; Yunita Aprilina; Sayfuddin Sayfuddin (Secure And Knowledge-Intelligent Research in Cybersecurity And Multimedia (SAKIRA), 2026)
The concepts of User Interface (UI) and User Experience (UX) design have evolved from mere aesthetic elements into critical factors that determine the success of web- and mobile-based applications. This study aims to analyze the influence of implementing UI/UX design concepts on usability, user engagement, and the success of both web and mobile applications. The research utilizes a qualitative method with a literature review approach, analyzing various books, scientific journals, and relevant design guidelines. The results of the study indicate that implementing a User-Centered Design approach oriented toward user needs can enhance ease of use (usability), reduce cognitive load, and increase user involvement (user engagement). Furthermore, the application of design guidelines such as Material Design and Human Interface Guidelines contributes to interface consistency, increased user satisfaction, and delivers a positive impact on business success through improved efficiency, conversion rates, and Return on Investment (ROI). A case study on Tokopedia demonstrates that the implementation of consistent design concepts is capable of creating a better user experience across various platforms. Consequently, integrating UI/UX concepts from the early stages of development is a crucial factor in producing web and mobile applications that are easy to use, user-oriented, and highly competitive.